The Significance of Serum C-Reactive Protein and Neutrophil–Lymphocyte Ratio in Predicting the Diagnostic Outcomes of Renal Mass Biopsy Procedure (Journal of Kidney Cancer, 2023)
This study aimed to investigate the predictive role of serum C-reactive protein (CRP) and neutrophil-to-lymphocyte ratio (NLR) on renal mass biopsy outcomes. A total of 71 patients with suspected kidney masses who underwent renal mass biopsy procedure between January 2017 and January 2021 were retrospectively evaluated. Pathological results after the procedure were obtained and pre-procedural serum CRP and NLR levels were extracted from the patients’ data. The patients were grouped into benign and malignant pathology groups according to the histopathology results. The parameters were compared between the groups. Diagnostic role of the parameters in terms of sensitivity, specificity, and positive and negative predictive values was also determined. Additionally, Pearson correlation analysis, and univariate and multivariate cox proportional hazard regression analyses were also performed to investigate the above association with tumor diameter and pathology results, respectively. At the end of the analyses, a total of 60 patients had malignant pathology on histopathological investigations of the mass biopsy specimens, whereas the remaining 11 patients had a benign pathological diagnosis. Significantly higher CRP and NLR levels were detected in the malignant pathology group. The parameters positively correlated with the malignant mass diameter, as well. Serum CRP and NLR determined the malignant masses before the biopsy with sensitivity and specificity of 76.6 and 81.8%, and 88.3 and 45.4%, respectively. Moreover, univariate and multivariate analyses showed that serum CRP level had a significant predictive value for malignant pathology (HR: 0.998, 95% CI: 0.940–0.967, P < 0.001 and HR: 0.951, 95% CI: 0.936–0.966, P < 0.001, respectively). In conclusion, serum CRP and NLR levels were significantly different in patients with malignant pathology after renal mass biopsy compared to the patients with benign pathology. Serum CRP level, in particular, diagnosed malignant pathologies with acceptable sensitivity and specificity values. Additionally, it had a substantial predictive role in determining the malign masses prior the biopsy. Therefore, pre-biopsy serum CRP and NLR levels may be used to predict the diagnostic outcomes of renal mass biopsy in clinical practice. Further studies with larger cohorts can prove our findings in the future.